Sistem Rekomendasi Wisata di Pekalongan melalui Chatbot dengan Framework Rasa - Fakhri; Kristiawan Nugroho (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Pekalongan, a city renowned for its batik and rich in cultural and natural attractions, has great potential in the tourism sector. However, limited access to integrated and easily accessible information poses challenges for tourists planning their trips. The Rasa-based Telegram chatbot addresses these challenges as an innovative solution. Through interactive engagement, tourists can receive recommendations for destinations, culinary spots, and other relevant information tailored to their preferences. This system leverages Rasa Natural Language Understanding (NLU) to interpret user queries and provide appropriate responses. Comprehensive tourism data of Pekalongan is embedded into the system to ensure accurate and relevant recommendations. The chatbot's evaluation includes direct user testing to measure the accuracy of recommendations, user satisfaction, and ease of use. Results indicate that the Rasa-based Telegram chatbot can deliver personalized and accurate recommendations, enhancing the travel planning experience for tourists visiting Pekalongan.